Common Fixed Point of Semi Compatible Maps in Fuzzy Metric Spaces - Chauhan, MS; Badshah, VH; Chouhan, Virendra Singh (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The purpose of this paper is to prove a common fixed point theorem on fuzzy metric space using the notion of semi compatibility, our result generalize the result of Som. Also, we are giving an example that make strong to our result. Keywords: Common fixed point; Fuzzy metric space; R-weakly commuting; Semi compatible maps. DOI: 10.3126/kuset.v6i1.3313 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp70-78